Thermodynamic analysis and purification for source materials in sublimation crystal growth of aluminum nitride - Du, Li; Edgar, James H. (Materials Research Society, 2020)
Source material purification according to a thermodynamic analysis is reported for the sublimation crystal growth of aluminum nitride in an inert reactor. OAlOH is strongly favored over all other possible oxygen containing compounds in both the Al-O-H-N and Al-O-H-C-N systems, while Al2O the most favorable oxygen containing gas species for Al-O-N system, become secondary favorable gas species. A low temperature (<1200 °C) treatment is effective in eliminating oxygen and hydrogen from the source powder. Carbon monoxide is another important oxygen containing gas species in the Al-O-H-C-N system, and is favored over Al2O at certain temperature and pressure. Carbothermal reduction with intentionally added carbon (graphite) can further reduce the oxygen concentration. Experiments show that high-temperature sintering minimizes the oxygen concentration and reduces the specific surface area of the source. With 5.5% of mass loss, source purification reduced impurities concentrations to 0.019±0.001wt%O, 7±1ppmH, and 0.010±0.004wt%C.
Keywords: Single crystal growth; Growth from vapor; Aluminum nitride; Thermodynamics